TRAF4‐Mediated LAMTOR1 Ubiquitination Promotes mTORC1 Activation and Inhibits the Inflammation‐Induced Colorectal Cancer Progression - Linlin Zhao; Ni Gao; Xiaoping Peng; Lei Chen; Tong Meng; Cong Jiang; Jiali Jin; Jiawen Zhang; Qiuhui Duan; Hongling Tian; Linjun Weng; Xinbo Wang; et al. (Advanced Science, 2024)
Abstract Mechanistic target of rapamycin complex 1 (mTORC1) is a conserved serine/threonine kinase that integrates various environmental signals to regulate cell growth and metabolism. mTORC1 activation requires tethering to lysosomes by the Ragulator‐Rag complex. However, the dynamic regulation of the interaction between Ragulator and Rag guanosine triphosphatase (GTPase) remains unclear. In this study, that LAMTOR1, an essential component of Ragulator, is dynamically ubiquitinated depending on amino acid abundance is reported. It is found that the E3 ligase TRAF4 directly interacts with LAMTOR1 and catalyzes the K63‐linked polyubiquitination of LAMTOR1 at K151. Ubiquitination of LAMTOR1 by TRAF4 promoted its binding to Rag GTPases and enhanced mTORC1 activation, K151R knock‐in or TRAF4 knock‐out blocks amino acid‐induced mTORC1 activation and accelerates the development of inflammation‐induced colon cancer. This study revealed that TRAF4‐mediated LAMTOR1 ubiquitination is a regulatory mechanism for mTORC1 activation and provides a therapeutic target for diseases involving mTORC1 dysregulation.